Modulation of peripheral CD4+CD25+Foxp3+ regulatory T cells ameliorates surgical stress-induced atherosclerotic plaque progression in ApoE-deficient mice - Handke, Jessica; Kummer, Laura; Weigand, Markus A.; Larmann, Jan (Frontiers in Cardiovascular Medicine, 2021)
Systemic inflammation associated with major surgery rapidly accelerates atherosclerotic plaque progression in mice. Regulatory T cells (Tregs) have emerged as important modulators of atherogenesis. In coronary artery disease patients, low frequency of Tregs constitutes an independent risk factor for cardiovascular complications after non-cardiac surgery. In this exploratory analysis, we investigate whether preoperative Treg levels affect surgery-induced atherosclerotic lesion destabilization in a murine model of perioperative stress. After 9 weeks of high-cholesterol diet, atherosclerotic apolipoprotein E-deficient mice with modulated Treg levels were subjected to a 30-minute surgical procedure consisting of general isoflurane anesthesia, laparotomy and moderate blood loss. Controls underwent general anesthesia only. Brachiocephalic arteries were harvested 3 days after the intervention for histomorphological analyses of atherosclerotic plaques. Tregs were depleted by a single dose of anti-CD25 monoclonal antibody (mAb) administered 6 days prior to the intervention. Expansion of Tregs was induced by daily injections of IL-2/anti-IL-2 complex (IL-2C) on three consecutive days starting 3 days before surgery. Isotype-matched antibodies and PBS served as controls. Antibody-mediated modulation was Treg-specific. IL-2C treatment resulted in an eight-fold elevation of peripheral CD4+CD25+Foxp3+ Tregs compared to mice administered with anti-CD25 mAb. In mice treated with PBS and anti-CD25 mAb, surgical stress response caused a significant increase of atherosclerotic plaque necrosis (PBS: p < 0.001; anti-CD25 mAb: p = 0.037). Preoperative Treg expansion abrogated perioperative necrotic core formation (p = 0.556) and significantly enhanced postoperative atherosclerotic plaque stability compared to PBS-treated mice (p = 0.036). Postoperative plaque volume (p = 0.960), stenosis (p = 0.693), lesional collagen (p = 0.258), as well as the relative macrophage (p = 0.625) and smooth muscle cell content (p = 0.178) remained largely unaffected by preoperative Treg levels. In atherosclerotic mice, therapeutic expansion of Tregs prior to major surgery mitigates rapid effects on perioperative stress-driven atherosclerotic plaque destabilization. Future studies will show, whether short-term interventions modulating perioperative inflammation qualify for prevention of cardiovascular events associated with major non-cardiac surgery.
Im Titel sind die Pluszeichen hochgestellt
Gesehen am 25.08.2021